2012
DOI: 10.1080/01488376.2012.696410
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress Experienced by Parents of Young Children With Congenital Heart Defects: A Comprehensive Review of Literature

Abstract: The purpose of this study was to examine the existing research on the psychological distress experienced by parents whose young children (between the ages of 0 and 5 years old) have a congenital heart defect (CHD). A more detailed understanding of the distress experienced by these parents, including stress associated with the child's age, the severity of the child's diagnosis, and parent characteristics, is vital as it would allow for more targeted and individualized support for this population to enhance pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 42 publications
2
50
0
Order By: Relevance
“…(6)(7)(8)(9) Research findings on parenting stress outcomes in children with CHD are conflicting, with some investigators reporting that parents experienced higher levels of stress, (1,6,7,10,11) whilst others have found stress levels to be similar to those experienced by parents of healthy children; in fact, in some instances parents of children with CHD have even reported lower stress levels than parents of healthy children. It has been suggested that these parents have likely developed a higher threshold for what they perceive to be stressful due to their experiences with their child with CHD.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…(6)(7)(8)(9) Research findings on parenting stress outcomes in children with CHD are conflicting, with some investigators reporting that parents experienced higher levels of stress, (1,6,7,10,11) whilst others have found stress levels to be similar to those experienced by parents of healthy children; in fact, in some instances parents of children with CHD have even reported lower stress levels than parents of healthy children. It has been suggested that these parents have likely developed a higher threshold for what they perceive to be stressful due to their experiences with their child with CHD.…”
Section: Introductionmentioning
confidence: 87%
“…Clinically significant stress levels would identify parents that would likely benefit from psychological and educational interventions. (5,18,26,40) These interventions may include counselling, parent education, active listening and the provision of anticipatory guidance, teaching of coping skills and developing strategies for accessing social support within parents' families and communities, and parent support groups have all been found to mediate stress and anxiety. (7,15,17,38,39) The PSI-SF has been used in several studies to determine parenting stress in children with CHD, and has been found to be a valid and reliable measure.…”
Section: Fortymentioning
confidence: 99%
See 3 more Smart Citations